ACE Inhibitory Peptides Derived from Muscovy Duck (Cairina moschata) Plasma - Zongshuai Zhu; Haoyu Guo; Yan Xu; Anthony Pius Bassey; Ahtisham Ali; Ming Huang; Jichao Huang (Foods, 2022)
In this study, angiotensin-converting enzyme inhibitory peptides (ACE–IPs) derived from Muscovy duck (Cairina moschata) plasma hydrolysate (MDPH) were investigated. According to the general research protocol for bioactive peptides, the crude ACE–IPs of Muscovy duck plasma were separated and purified by ultrafiltration, gel chromatography and reversed-phase high-performance liquid chromatography (RP–HPLC). Then the components with the highest ACE inhibition potential were selected for identification. Finally, the inhibition mechanism was explored by molecular docking and in silico simulated digestion. A total of 121 peptides was detected, and five were screened for synthesis verification and molecular docking. The peptide VALSSLRP revealed high ACE inhibitory activity (91.67 ± 0.73%) because this peptide bound tightly to the S1′ pocket and formed 3 hydrogen bonds. Meaningfully, this work provides some new information about the generation of ACE–IPs derived from duck blood plasma.